A public health approach to patient-centredness in embryo research - Samorinha, C.; Machado, H.; Freitas, C. de.; Amorim, M.; Silva, S. (European Journal of Public Health, 2016)
Looking at patient-centredness through the lens of public health is needed for responsible governance of human embryo research. This study aimed to explore patients’ experiences and perspectives on information about and consent for research with human embryos, to sustain the development of policies and guidelines.